Otimização de controladores utilizando algoritmos genéticos para melhoria da capacidade de sobrevivência a afundamentos de tensão de aerogeradores de indução duplamente excitados - VIEIRA, João Paulo Abreu (Universidade Federal do Pará, 2011)
It is proposed in this thesis a methodology to obtain optimal controllers gains for the rotorside converter of doubly fed induction generators (DFIGs) using a genetic algorithm approach. The main objective is to enhance the operational security and robustness of the power system, by a more effective contribution of the DFIG controllers to the system controllability. To reach this goal, the crow-bar protection scheme is activated during the fault period when severe voltage sags occur in order to maintain the rotor-side converter connected to the DFIG. Immediately after the fault is cleared the crow-bar protection scheme is deactivated and simultaneously the rotor-side converter optimal controllers are turned on which permits the improvement of the converter ride-through capability and also contribute to enhance the overall power system stability margin. The effectiveness of this proposed methodology was assessed for the DFIG-based plants using a real electrical network, in three different operational conditions.